2002
DOI: 10.1002/app.11094
|View full text |Cite
|
Sign up to set email alerts
|

New conductive thermoplastic elastomers. Part II. Physical and chemical‐physical characterization

Abstract: ABSTRACT:To overcome the problems relevant to the low processbility and scarce mechanical properties of polyaniline, in a previous work we have proposed the synthesis of elastomeric conducting copolymers prepared by grafting polyaniline (EB) or sulfonated polyaniline (SPAN) chains to the backbone of a carboxylated segmented polyurethane (PEUA). In the present work the physical and chemicalphysical properties of the copolymers are investigated. As evidenced by thermal (DSC) and dynamo-mechanical (DMTA) characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Such behavior also has been observed for composites prepared by mixing polyaniline with plastic26 or elastomeric24 polymers and for polyurethane/polyaniline‐conducting copolymers, described in previous articles 2, 27. However, the increase in conductivity observed in the present work is higher than that found previously.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Such behavior also has been observed for composites prepared by mixing polyaniline with plastic26 or elastomeric24 polymers and for polyurethane/polyaniline‐conducting copolymers, described in previous articles 2, 27. However, the increase in conductivity observed in the present work is higher than that found previously.…”
Section: Resultssupporting
confidence: 81%
“…In previous articles we described the synthesis1 and the physical and chemical physical characterization2 of new elastomeric copolymers obtained by grafting polyaniline (EB) or sulfonated polyaniline (SPAN) to a carboxylated segmented polyurethane (PEUA). However, the overall procedure is a quite time‐consuming process, including (a) synthesizing the noncommercial insulating matrix (typically carried out in two steps),(b) grafting the conducting polymer, and (c) eventually performing the crosslinking reaction (necessary to improve the mechanical properties of the material).…”
Section: Introductionmentioning
confidence: 99%
“…Carone et al [77,78] observed that when elastomeric conducting copolymers prepared by grafting polyaniline (EB) or sulfonated polyaniline (SPAN) chains to the backbone of a carboxylated segmented polyurethane are HCl doped, their electrical conductivity increases many orders of magnitude, reaching values of about 10 -3 S/cm. Stretching the copolymer films may further increase the conductivity, measured along the deformation direction.…”
Section: Preparation Of Tpu-polythiophene Compositesmentioning
confidence: 99%
“…To overcome the problems relevant to the low processability and scarce mechanical properties of polyaniline, Carone et al[77] proposed the synthesis of elastomeric conducting copolymers prepared by grafting polyaniline (EB) or sulfonated polyaniline (SPANI) chains to the backbone of a carboxylated segmented polyurethane. In a more recent work[78] the researchers investigated the physical and chemical-physical properties of the copolymers. As evidenced by DSC and DMTA characterization, the introduction of EB or SPANI in the modified PU matrix enhances the hard-soft phase segregation effect, because of the strong tendency of the conductive polymer chains to aggregate.…”
mentioning
confidence: 99%
“…Intrinsically conductive polymers (e.g., polyaniline) and their “buckytubes” that lead to the formation of microtubules instead of spheres13, 14 may help to overcome the above‐mentioned problems. By stretching the intrinsic electrically conductive polymer alone, an increase of the polymer's conductivity along the orientation axis could be observed 15–18…”
Section: Introductionmentioning
confidence: 99%